The impact of humanitarian food assistance on household food security during conflict in Mali - Gelli, Aulo; Tranchant, Jean-Pierre (International Food Policy Research Institute, 2018)
The chapter is centered on assessing the impact of WFP’s food assistance on the food security and nutrition outcomes of rural households in the Mopti region of Mali. In our assessment, we relied on data from a unique precrisis baseline to design a longitudinal, quasi-experimental study based on two survey rounds executed five years apart. Data were collected from 66 communities randomly selected from within food-insecure districts. Study outcomes included household expenditures, food consumption (measured through seven-day recall), and nutritional status in children from two to five years of age.